P50 Synthetic lethality in liver cancer cell lines treated with inhibitors of DNA double-strand break repair. (16th November 2010) - Reeves, H; Cornell, L; Munck, J; Budhisetiawan, F; Newell, D; Bardos, J; Manas, D; Nicola, C; Reeves, H
Abstract : Introduction: DNA double-strand breaks (DSBs) are the most cytotoxic lesions induced by ionising radiation (IR) and anticancer drugs, such as topoisomerase II poisons (eg, doxorubicin). The major DSB repair pathways are non-homologous end joining (NHEJ) and homologous recombination (HR), in which DNA-Dependent Protein Kinase (DNA-PK) and ataxia telangiectasia mutated (ATM) are key components. DNA-PK in particular is up-regulated in hepatocellular carcinoma, (GEO profiles) possibly contributing to resistance to cytotoxic therapies. Aim: To assess DNA-PK and ATM as therapeutic targets for chemo- and radio-sensitisation in hepatoma. Method: Basal protein levels and activities were determined by Western blot analysis in hepatoma cell lines. DNA-PK and ATM activity following doxorubicin stimulation was measured using antibodies specific to phosphorylated Ser-2056 DNA-PKcs and phosphorylated Ser-1981 ATM. DSB repair was measured by immunofluorescence detection of γ-H2AX foci. Cell survival was determined by clonogenic assay. Results: We demonstrated high basal levels of DNA-PK in three hepatoma cell lines (Huh7, Hep3B and HepG2), with DNA-PK activation induced by 0.25 μM doxorubicin. Despite similar DNA-PK activation, we observed differential sensitivity to doxorubicin (7%, 49% and 75% survival at 10 nM doxorubicin in Huh7, Hep3B and HepG2, respectively). HepG2 cells with the greatest resistance to doxorubicin displayed a 10-fold activation of ATM relative to the other cell lines. The DNA-PK inhibitor NU7441, increased doxorubicin and ionising radiation (IR) induced cytotoxicity in all cell lines (1.3 up to fourfold), correlating with a reduction in DSB repair measured by γ-H2AX foci. Importantly, in doxorubicin resistant HepG2 cells, while incubation with NU7441 or the ATM inhibitor (KU55933) alone, had minimal effects on cell survival (91% and 86%, respectively), their combination in the absence of a cytotoxic agent markedly inhibited cell survival (21%; p<0.001, ANOVA). The addition of 10 nM doxorubicin reduced survival to less than 5% of colonies. Conclusion: These findings support the clinical application of DNA-PK and ATM inhibitors as chemo- and radio-sensitisors in hepatoma patients. Furthermore, these data suggest that hepatoma cell survival is dependent on up-regulation of DSB repair, effected by either DNA-PK or ATM, and that inhibition of both induces synthetic lethality—preventing DSB repair by both NHEJ and HR. The therapeutic implication is that in combination, these agents could be used to specifically induce cancer cell death, with minimal toxicity to surrounding liver tissues.